Interpretation within the context of francophone African literature: an investigation (2015)
African literature is a part of translation studies. Whoever writes in a language different from his/her mother tongue is translating. Therefore, writers of francophone African origin are translators. The discipline of Translation studies has two major branches, which are translation and interpretation. In some novels of African origin, the interpreter plays an important role, useful in understanding the message of the author. The objective of this article is to evaluate and understand the relevance of interpretation within African fiction of francophone origin namely, Les soleils des independences of Ahmadou Kourouma, Les bouts de bois de Dieu of Sembene Ousmane and L'etrange destin de Wangrin: les roueries d'wi interpret africain (1992) of Ahmadou Hampath6 Ba. The study adopts not only historical, but comparative and narrative analysis of data from the texts of Ahmadou Kourouma, Sembene Ousmane, and Ahmadou Hampathe Ba, while the theoretical framework is descriptive translation studies (DTS). Works of linguists, translators, language experts, and literary' scholars serve as reference documents. The profession of translator is a mere transposition of the function of the griot as known in francophone Africa, and the commandant in the novel stands as the emperor of the oral literature where the griot is a professional linguist that facilitates the communication between the emperor and his subjects. The study concludes on the notes that the griot and the interpreter are lucky individuals who hold a privilege position and who at the same time must be checked because they go beyond the limit of their duty.